Integrative Analysis Identified a 6-miRNA Prognostic Signature in Nasopharyngeal Carcinoma - Chen, Yunqin; Wang, Zhen; Li, Hong; Li, Yixue (Frontiers in Cell and Developmental Biology, 2021)
Backgrounds: Nasopharyngeal carcinoma (NPC) is an Epstein-Barr virus-associated epithelial malignancy, which is rare in America but endemic in China. The current clinical gold TNM-based standard for prognosis may not be enough. Although some studies have reported some miRNAs have a prognostic power in NPC, there is a scarcity of independent validation for these miRNAs. Methods: In this work, we firstly literature reviewed all miRNA profiling datasets with survival information, then integrated miRNA expression data across different profiling platforms and built prognostic models using machine learning methods. The Kaplan-Meier method and log-rank tests were applied to estimate correlations of the miRNA signature with survival, and the area under the time-dependent ROC curve (AUC) and concordance index (C-index) were used to assess the predictive power of prognostic models. We also investigated the biological roles of the prognostic miRNAs through identifying their regulated genes and association with immune infiltration. Results: We constructed a prognostic model based on 6-miRNA signature (ebv-miR-BART12, ebv-miR-BART15,miR-29c-3p ,miR-30e-5p, hsa-miR-375-3p,has-miR-93-5p) using the elastic net penalized Cox regression model. The AUCs of our model predicted 1-, 3-, 5-year overall survival rate were 0.90, 0.73, 0.70 for external test dataset, and showed better prognostic power than models using previously reported miRNA signatures. The 6-miRNA risk score was an independent prognostic predictor for overall survival (OS), disease-free survival (DFS) and metastasis-free survival (MFS). It could stratify patients into low-risk and high-risk groups; patients in low-risk group treated with concurrent chemotherapy had a better survival. On the basis that the 6-miRNA risk score improved the current clinical gold standard for prognosis, we built a nomogram integrating both clinical characterizations and the risk score to predict 3-,5- and 10-year overall survival. Functional analysis suggested the 6 miRNAs mainly play roles in virus infection pathways and oncogenic signaling pathways and associated with B cell expression. Conclusion: We identified a 6-miRNA prognostic signature in nasopharyngeal carcinoma across miRNA profiling platforms and patient geographical difference, which showed good prediction capability in terms of OS, DFS and MFS. The 6-miRNA risk score might be helpful for clinician make treatment strategies and predict patients outcome.